Kajian Perbandingan Pengaturan Arbitrase dalam Sengketa Teknologi Kecerdasan Buatan (AI) dari Perspektif Hukum Indonesia dan Uni Eropa - Liem Gai Sin; Wika Yudha Shanty; Ariyanti Ariyanti (Society, 2025)
Artificial Intelligence (AI) has generated new forms of technology disputes involving algorithmic opacity, data governance, liability allocation, and cross-border contractual relations. These disputes challenge conventional dispute resolution mechanisms and increase the relevance of arbitration as a flexible, confidential, and expert-oriented forum. This study examines the regulation of arbitration in AI technology disputes from the perspective of Indonesian and European Union law. Using normative legal research with statutory and comparative approaches, it analyses Indonesia’s Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution and compares it with the European Union’s AI and digital governance framework. The findings show that Indonesia’s arbitration framework remains general and insufficiently prepared for AI-related disputes due to the absence of AI-specific regulation, evidentiary imbalance, limited institutional readiness, and an underdeveloped public policy framework for algorithmic risks. By contrast, the European Union provides more developed substantive standards through the EU Artificial Intelligence Act, the General Data Protection Regulation, and related digital regulations, although it does not establish a specific arbitration regime for AI disputes. This study argues that Indonesia needs adaptive arbitration reform through AI-specific regulation, strengthened arbitral expertise, digital evidence mechanisms, and technology-sensitive arbitration clauses.